Real-world effectiveness of pembrolizumab as first-line therapy for cisplatin-ineligible patients with advanced urothelial carcinoma: the ARON-2 study - Santoni, Matteo; Myint, Zin W; Büttner, Thomas; Takeshita, Hideki; Okada, Yohei; Lam, Elaine T; Gilbert, Danielle; Küronya, Zsófia; Tural, Deniz; Pichler, Renate; Grande, Enrique; Crabb, Simon J; et al. (Cancer immunology, immunotherapy, 2023)
BACKGROUND: The advent of immune-checkpoint inhibitors has challenged previous treatment paradigms for advanced urothelial carcinoma (UC) in the post-platinum setting as well as in the first-line setting for cisplatin-ineligible patients. In this study, we investigated the effectiveness of pembrolizumab as first-line treatment for cisplatin-ineligible UC. METHODS: Data from patients aged ≥ 18 years with cisplatin-ineligible UC and receiving first-line pembrolizumab from January 1st 2017 to September 1st 2022 were collected. Cisplatin ineligibility was defined according to the Galsky criteria. Thirty-three Institutions from 18 countries were involved in the ARON-2 study. RESULTS: Our analysis included 162 patients. The median follow-up time was 18.9 months (95%CI 15.3-76.9). In the overall study population, the median OS was 15.8 months (95%CI 11.3-32.4). The median OS was significantly longer in males versus females while no statistically significant differences were observed between patients aged < 65y versus ≥ 65y and between smokers and non-smokers. According to Recist 1.1 criteria, 26 patients (16%) experienced CR, 32 (20%) PR, 39 (24%) SD and 55 (34%) PD. CONCLUSIONS: Our data confirm the role of pembrolizumab as first-line therapy for cisplatin-unfit patients. Further studies investigating the biological and immunological characteristics of UC patients are warranted in order to optimize the outcome of patients receiving immunotherapy in this setting.
Keywords: Humans; cisplatina; Pembrolizumab; Cisplatin; karcinom z přechodných buněk; NCT05290038; Female; protokoly protinádorové kombinované chemoterapie; lidé; humanizované monoklonální protilátky; Immunotherapy; Antibodies, Monoclonal, Humanized; ženské pohlaví; ARON-2 study; Male; nádory močového měchýře; Antineoplastic Combined Chemotherapy Protocols; Carcinoma, Transitional Cell; mužské pohlaví; Urinary Bladder Neoplasms; Real-world data; Urothelial cancer